2021
DOI: 10.1183/13993003.01724-2021
|View full text |Cite
|
Sign up to set email alerts
|

Early high antibody titre convalescent plasma for hospitalised COVID-19 patients: DAWn-plasma

Abstract: BackgroundSeveral randomised clinical trials have studied convalescent plasma for coronavirus disease 2019 (COVID-19) using different protocols, with different severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralising antibody titres, at different time-points and severities of illness.MethodsIn the prospective multicentre DAWn-plasma trial, adult patients hospitalised with COVID-19 were randomised to 4 units of open-label convalescent plasma combined with standard of care (intervention group) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 24 publications
(23 reference statements)
0
47
0
Order By: Relevance
“…A total of 49 RCTs ( N = 43,943) reported the incidence of mortality. Excluding five studies using plasma controls [ 26 – 30 ], 44 studies ( N = 42,604) [ 15 19 , 22 , 31 , 41 49 , 52 55 , 57 70 , 72 , 74 82 ] were included in the NMA. Follow-up durations for mortality ranged from 30 to 90 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 49 RCTs ( N = 43,943) reported the incidence of mortality. Excluding five studies using plasma controls [ 26 – 30 ], 44 studies ( N = 42,604) [ 15 19 , 22 , 31 , 41 49 , 52 55 , 57 70 , 72 , 74 82 ] were included in the NMA. Follow-up durations for mortality ranged from 30 to 90 days.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 19 studies [ 17 , 19 , 22 , 41 , 43 , 44 , 47 49 , 51 , 52 , 57 , 60 , 63 , 68 , 70 , 73 , 77 , 81 ] ( N = 26,912) reported the incidence of progression to invasive mechanical ventilation and/or ECMO and were included in the NMA. No intervention was associated with significant reductions in the odds of invasive mechanical ventilation/ECMO (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The VNT differs according to the type of replication- competent cell line, the viral isolate used for the challenge (which is critically important when the virus is mutating rapidly as has been the case with emergence of variants of concern), the multiplicity of infection (i.e., the ratio between the viral inoculum - referred with different measuring units – and the number of replication-competent cells within each well), the detection system (optic microscopy for cytopathic effect, immunostaining, quantitative PCR, or luminometer for engineered pseudoviruses), and finally the threshold of neutralization (50% or 90%). The DAWN-plasma (33), C3PO (27), and REMAP-CAP (34) RCTs provide clear examples of such heterogeneity, with up to 4 different VNTs used at different participating laboratories/countries within the same study (see Table 1). It was not until August 2020, when many trials were already underway, that the FDA Emergency Use Authorization 26382 defined high-titer CCP on the basis of correlation with a reference standard, the Broad Institute live-virus, 5-dilution VNT as a 50% inhibitory dilution (ID 50 ) of 1:250 or more (https://www.fda.gov/media/141481/download), and exclusive use of high-titer CCP was formally recommended by the FDA only on March 9, 2021 Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than pooling published RCTs, the Continuous Monitoring of Pooled International Trials of Convalescent Plasma for COVID-19 Hospitalized Patients (COMPILE) study pooled individual patient data from ongoing RCTs at two-week intervals. Unfortunately, with the single exception of CONTAIN (26), participating RCTs largely shared usage in advanced disease stages (DAWN-plasma (33), PLACID (10), ConCOVID (35), ConPlas-19 (47), NCT04421404, PennCCP2 (88), and the Brasília Covid-19 Convalescent Plasma (BCCP)) (89).…”
Section: Resultsmentioning
confidence: 99%
“…Additional observational studies and RCTs of CCP were subsequently published or made publicly available through pre‐print posting. In the hospitalized population, RCTs include the PLACID (India), 31 PlasmAr (Argentina), 32 RECOVERY (UK), 33 REMAP‐CAP (UK), 34 CONCOR‐1 (Canada, US, Brazil), 35 TSUNAMI (Italy), 36 ConPlas‐19 (Spain), 37 CAPSID (Germany), 38 DAWn‐Plasma (Belgium), 39 Balcells et al (Chile), 40 Ray et al (India), 41 Bennett‐Guerrero et al (US), 42 and CONTAIN (US) 43 trials, which found no improvement in their primary clinical endpoints in patients treated with CCP compared to control subjects. In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28‐day mortality, and a double‐blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival.…”
Section: Discussionmentioning
confidence: 99%